4‐Sulfonyloxy/alkoxy benzoxazolone derivatives with high anti‐inflammatory activities: Synthesis, biological evaluation, and mechanims of action via p38/ERK‐NF‐κB/iNOS pathway. (22nd September 2020) - Tang, Li; Luo, Jie‐ran; Wang, Xiao‐yan; Zhao, Bei; Ge, Rui; Liang, Tai‐gang; Ban, Shu‐rong; Li, Qing‐shan
Abstract: In an effort to discover new agents with high anti‐inflammatory activity, 22 new 4‐sulfonyloxy/alkoxy benzoxazolone derivatives were synthesized, characterized, and evaluated for their anti‐inflammatory activities against lipopolysaccharide (LPS)‐induced nitric oxide (NO) production and TNF‐α expression in RAW 264.7 cells in vitro. Most of these compounds displayed greater inhibitory ability against NO production than the lead compound 4‐ o ‐methyl‐benzenesulfonyl benzoxazolone, and the most active compound 2h exhibited the strongest inhibitory activity against NO, IL‐1β, and IL‐6 production with IC50 values 17.67, 20.07, and 8.61 μΜ, respectively. The effects of 2h were comparable or stronger than those of the positive control celecoxib. Compound 2h also displayed higher activity in vivo than celecoxib in a mouse model of xylene‐induced ear edema, based on their inhibitory rates of 42.69% and 30.87%, respectively. Further molecular analysis revealed that compound 2h significantly reduced the iNOS levels in cell supernatant and suppressed the protein expression of iNOS, p‐p38, p‐ERK, and nuclear NF‐κB. The results indicated that the anti‐inflammatory effect of 2h might be realized through the regulation of ERK‐ and p38‐mediated mitogen‐activated protein kinase (MAPK)‐NF‐κB/iNOS signaling, thereby reducing the excessive release of NO, IL‐1β, and IL‐6. Our findings demonstrated that compound 2h, a new benzoxazolone derivative, could inhibit activation of the MAPK‐NF‐κB/iNOS pathway, supporting its potential as a novel anti‐inflammatory agent. Abstract : New 4‐sulfonyloxy/alkoxy benzoxazolone derivatives were prepared and identified, and the activities against lipopolysaccharide‐stimulated inflammatory response in vitro were evaluated. 2h could inhibit the activation of mitogen‐activated protein kinase‐NF‐κB/iNOS pathway to play anti‐inflammatory activity. 2h could form hydrogen bonds with iNOS to affect the anti‐inflammatory activity directly or indirectly, and 2h was a potential iNOS inhibitor.